A positive association between food insecurity and the prevalence of overactive bladder in U.S. adults - Xiao, Yunfei; Yin, Shan; Bai, Yunjin; Wang, Jiahao; Cui, Jianwei; Yang, Yaqing; Wang, Jia (Frontiers in Nutrition, 2024)
Objective This study aims to examine the correlation between overactive bladder (OAB) and food insecurity. Methods We conducted a cross-sectional analysis utilizing extensive population data derived from the National Health and Nutrition Examination Survey 2007–2018. The status of Household food insecurity is evaluated by the US Food Security Survey Module. To explore the relationship between food insecurity and OAB, three multivariable logistic regression models were carried out. Additionally, interaction and stratified analyses were also performed to find whether some factors have the potential to alter the correlation. Results There were 29,129 participants enrolled in the study. Compared to the other three groups, individuals with full food security exhibited a lower proportion of nocturia, urinary urgency incontinence, and OAB. In the fully-adjusted model, it was found that people experiencing food insecurity have a significantly higher prevalence of OAB compared to those with food security in the fully-adjusted model (OR = 1.540, 95%CI 1.359–1.745). Additionally, there was a significant association between the levels of food insecurity and an increased risk of OAB prevalence was also observed (marginal food security: OR = 1.312, low food security: OR = 1.559, and very low food security: OR = 1.759). No significant interaction was seen in the fully-adjusted model. Conclusion There is a strong positive correlation between food insecurity and the prevalence of OAB. Similarly, the correlation between levels of food insecurity and OAB also indicates the same trend. Namely, the more insecure food, the higher risk of OAB prevalence in the population.